If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q + -2(3) + 4 = 0 Multiply -2 * 3 q + -6 + 4 = 0 Reorder the terms: -6 + 4 + q = 0 Combine like terms: -6 + 4 = -2 -2 + q = 0 Solving -2 + q = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + q = 0 + 2 Combine like terms: -2 + 2 = 0 0 + q = 0 + 2 q = 0 + 2 Combine like terms: 0 + 2 = 2 q = 2 Simplifying q = 2
| .5(60x)+300x=p | | q-2(1)+4=0 | | q-2+4=0 | | q-2(0)+4=0 | | .8x=x-18 | | q-2p+4=0 | | 2v^2+7=-6 | | 4w^2=-20w-25 | | .80x=x-18 | | 5x+18=8x+27 | | 4+x=10+0.5x | | 3XY+5Y=7 | | (x-2)x=3x(2x+1) | | 58=-2(m+4)m | | r^2-19t+18=0 | | r^2-9t+18=0 | | 1000=x(30-2x)(20-2x) | | -30a=-20 | | -30=-20 | | 7x-14=11x | | -2x-4=24 | | -2(2x-6)=20 | | -2(x+5)=30 | | 2(2x-6)=40 | | 4x-2x+2=16 | | x-5x+4=-8 | | 2x+8x=17 | | -7x+5x+2=20 | | x-8-3=10 | | 8z=40 | | 24x-3=15+45x | | 9t=-16t^2+60t |